Intellectual Property Within the Emerging Renewable Energy Market: A Case Study of the Eu - Ramona Miron; Simona Gabor (CES Working Papers, 2012)
Energy produced from renewable sources and its capacity to reduce GHG emissions and to enhance energy security is one of today's most debated issues. The renewable energy sources form a small but fast growing part of the global energy portfolio. A crucial condition for green energy to win an important share of the energy sector is lowering the production cost of the equipments. In the long run this can be achieved by supporting and protecting innovation in this field. This paper deals with the debated issue of intellectual property in the field of renewable energy in the European Union. We start with a study of the legislative framework of both intellectual property and renewable energy. Using statistical data and illustrative case studies the paper aims to determine the characteristics and importance of intellectual property in the field of renewable energy. We look at the EU as a regional player and analyse the influence of intellectual property both internally – by presenting the different discourses of developed and developing EU countries - and externally – on global level.
Keywords: O33; O34; O38; Q28; Q42; 330; renewable energy; intellectual property; European policies Romania